SPATIAL QUOTIENT IMPROVEMENT THROUGH THE DEVELOPMENT OF BRAINSTORMING LEARNING METHOD BASED ON SOFTWARE GRAPHMATICA RESEARCH OPERATION LINEAR PROGRAM - Abdul Aziz; Iswahyudi Joko Suprayitno (Universitas Muhammadiyah Semarang, 2017)
The aim of this research and development was to know the effect of the brainstorming model based on software graphmatica on spatial quotient research operation linear program. Graphmatica is a tool that plans calculationswith numbers and calculus facilities. Combining cartesian chart functions, relationships and equations, parameters, polarization and ordinary differential equations, has about 999 graphs. In addition Graphmatica also has the ability to break the sequence of numbers and display tangent, integral and clear lines. This tool can be applied from secondary school to college. Spatial intelligence is the ability to think someone mengimajinasikan an object in the form of images and space. The development of this product uses a literature study to strengthen the development of a product. This educational product is in the form of Brainstorming learning method and software (software) Graphmatica. Through this stage will examine the scope of Brainstorming and SoftwareGraphmatica methods, the breadth of use, supporting conditions for the product to be used or implementedoptimally, and its advantages and limitations. A literature study is also needed to determine the most appropriatesteps in the development of the product. In the results of the linear program exam as much as 19 muhammadiyah university students showed good learning outcomes after applying the development of software product graphmatica. This shows that there is an influence in the development of graphmatica software products with the brainstorming model of linear program learning outcomes.Keywords: Spatial Quotient, Brainstorming, Software Graphmatica